2022
DOI: 10.1021/acsami.2c10746
|View full text |Cite
|
Sign up to set email alerts
|

Paper-Derived Millimeter-Thick Yarn Supercapacitors Enabling High Volumetric Energy Density

Abstract: Solid-state supercapacitors have shown extraordinary promise for flexible and wearable electronics. To date, they are still limited by relatively poor energy volumetric performances, which are largely determined by the pore structures and physicochemical properties of electrode materials. Moreover, the poor mechanical properties afforded because of the intrinsic shortcomings of electrode materials need to be resolved. Herein, we designed a flexible and solid-state yarn electrode with high porosity and high aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…This is because the rise in temperature accelerates the ow of electrolyte ions in the APC-PVA@ZnCl 2 supercapacitor, which enables more electrolyte ions to reach the interior of the electrode material bulk phase, thus effectively improving the specic capacitance of the supercapacitor. On the whole, these volumetric specic capacitance values can be compared to some previous literature works, [34][35][36][37] as displayed in Fig. 4c.…”
Section: Structure and Morphologymentioning
confidence: 93%
See 1 more Smart Citation
“…This is because the rise in temperature accelerates the ow of electrolyte ions in the APC-PVA@ZnCl 2 supercapacitor, which enables more electrolyte ions to reach the interior of the electrode material bulk phase, thus effectively improving the specic capacitance of the supercapacitor. On the whole, these volumetric specic capacitance values can be compared to some previous literature works, [34][35][36][37] as displayed in Fig. 4c.…”
Section: Structure and Morphologymentioning
confidence: 93%
“…4c and d) displays comparison maps of volumetric specic capacitance and energy density of APC-PVA@ZnCl 2 with reported works. [34][35][36][37][38][39][40][41][42] It is obvious that our work can be compared with those excellent works in recent years. All in all, these results demonstrate that the APC-PVA@ZnCl 2 supercapacitor has excellent environmental adaptability, showing its potential application value in different environments.…”
Section: Structure and Morphologymentioning
confidence: 99%
“…The results show that the electrode (PEDOT/CP-10) after 10 polymerization shows excellent conductivity (14 Ω/square) and a volume ratio capacitance of 13.7F cm -3 . Similarly, Heo et al [100] obtained conductive KHO (C-KHP) by loading Korean conventional paper (KHP) with a loaded conductive ink. Then the PEODT is loaded on C-KHP by gas phase polymerization to obtain PC-KHP paper-based composite electrode material.…”
Section: Cellulose/conductive Polymer Paper-based Composite Electrodementioning
confidence: 99%
“…Supercapacitors are being researched extensively in smart electronics applications such as flexible, biodegradable, transparent, wearable, flexible, on-chip, and portable energy storage. In comparison with conventional capacitors, supercapacitors use materials with a high specific surface area as electrodes [ 8 , 9 ]. A higher specific surface area and thinner dielectrics result in greater specific capacitance and energy density.…”
Section: Introductionmentioning
confidence: 99%
“…Supercapacitors have many other advantages, such as being environmentally friendly, having a long service life, being able to operate in wide temperature ranges, and being good at retaining charge even when large currents are applied; they are widely used in consumer electronics, smart meters, and transport [ 7 , 8 , 9 , 10 ]. Supercapacitors have shown that they can perform very well in some applications, but there are still several shortcomings that are relevant in some applications.…”
Section: Introductionmentioning
confidence: 99%